The Depersonalized as Vanishing Hero and Heroine in Yorùbá Moral Placards - Olatunde Bayo Lawuyi (Yoruba Studies Review)
The paper critically examines the relationship between the idea of moral placards and the existence of Yorùbá heroes and heroines. It takes as its starting point the philosophical import of the Yoruba proverb. Ọjọ́ a bá kú là ń dère, èèyàn ò sunwọ̀n láàyè (It is on the day one dies that one becomes an idol; no one is appreciated when alive). The paper argues that in the imagination, reality, and social constructions of the Yorùbá, desirable existence would make the dead, and not a living person, a deity, hero or heroine. It further argues that because Yorùbá society permits the co-existence and co[1]extensiveness of individual and public moral placards which is not regarded as an entirely closed system, an otherwise depersonalized person can later become a hero/deity/heroine. Basically, therefore, public moral placard can be revised to accommodate new values, give rise to new class of people, and establish for them an enviable status. These arguments are then deployed to the understanding of the nature of heroes and heroines within the Nigerian post-independence polity.